Energy Consumption, Exports, Foreign Direct Investment, and Economic Growth in ASEAN-5: The Mediating Role of Greenhouse Gas Emissions - Bahrul Ulum Rusydi; Baso Iwang; Radiatul Adwia (Faculty of Economics, Universitas Sriwijaya, 2026)
This study examines how greenhouse gas (GHG) emissions mediate the relationships between per capita energy consumption, exports, foreign direct investment (FDI), and economic growth in the ASEAN-5 economies. A panel of Indonesia, Malaysia, the Philippines, Singapore, and Thailand from 1991 to 2023 is estimated using two linked panel-regression equations. Estimator selection follows the Chow and Hausman tests, and indirect effects are evaluated using the Sobel product-of-coefficients test. The results show that per capita energy consumption and FDI significantly increase GHG emissions, whereas exports reduce them. In the growth equation, energy consumption and exports have negative direct associations at the 10 percent level, FDI has a positive association at the 5 percent level, and GHG emissions have a negative association at the 5 percent level. All three indirect effects are statistically significant, the emission channel reinforces the negative relationship between energy and growth, offsets part of the negative relationship between exports and growth, and reduces the positive contribution of FDI to growth. The study's main contribution is to demonstrate that a common environmental mediator operates differently across major growth drivers. The findings support ASEAN strategies centered on energy productivity, low-carbon export upgrading, green-FDI screening, and interoperable regional carbon-management frameworks.